The Demarcation of Punctuation Marks Int the Dictionaries of Linguistic Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this entry, we discuss the dictionary entry provides more details. It is said that the exchange of sounds is associated with other phenomena. As shown above, it is better to provide details in this entry rather than refer to another dictionary entry. If the dictionary is in electronic form, a hyperlink can be set. In it, the desired word is matched to the hyperlink function. As a result, when you click on that word, a separate window will open and you can read the link. Traditional / paper dictionaries or electronic dictionaries without a search engine (in pdf format) are not suitable for referencing. It takes up the student's time and leads to the division of his attention.